Laparoscopic vs open insertion of feeding gastrostomy tube in adults with head and neck cancers: A case‐matched comparative study. Issue 4 (15th December 2020) - Omari, Balqees; Asmer, Huthaifa; Al‐Najjar, Hani; Mohamad, Issa; Al‐Saraireh, Omar; Ammori, Basil J.
Abstract: Background: Patients with head and neck cancers may require feeding tube gastrostomy (FTG) during their treatment. Surgical gastrostomy is indicated in patients who fail or unsuitable for endoscopic or radiologic FTG insertion. Objective: The aim of this study was to compare the outcomes of a novel laparoscopic technique to the insertion of feeding tube gastrostomy (FTG) in patients with head and neck cancer vs conventional open surgery. Methods: Patients were randomly matched on a 1:1 basis according to whether the procedure was therapeutic or prophylactic and whether a concomitant less major surgical procedure was required. Results: The groups (17 patients in each group) were comparable for age, sex distribution, ASA score, body mass index, serum albumin levels and the frequencies of previous upper abdominal surgery, hypoalbuminaemia and prior chemoradiotherapy and/or cancer surgery. There were no conversions to open surgery. No significant differences were detected between the groups with regard to the operating time (median, 40 vs 60 minutes, P = .053) and 30‐day clinically significant morbidity (17.6% vs 23.5%, P = .180) or mortality (11.8% in each group). However, laparoscopy was associated with significantly shorter hospital stay (0 vs 2.8 days, P < .001) and greater proportion of day‐case procedures (64.7% vs 0%, P < .001). Conclusions: Laparoscopic insertion of FTG is safe, can be performed as a day‐case procedure, and is associated with shorter hospital stay compared with open surgery; it should be preferred over open surgery where local expertise exists.